Razvoj otrokovega vida - Lenassi, Eva (Medicinski razgledi, 2007)
The study of visual pathway maturation in children is still an active field ofresearch. Morphological and functional changes are most pronounced during the first few years of human life, when central retina, as well as the myelinisation of the visual pathway and visual cortex are developing fast. Maturation of the visual pathway can be studied by clinical and electrophysiological evaluation. Functioning of the retina can be objectively studied using electroretinography (ERG) and functioning of the rest of the visual pathway using visual evoked potentials (VEP). Our aim was to investigate the developmental changes of visual function in healthy infants and preschool children via clinical evaluation of visual acuity and with the use of electrophysiological methods. The correlation of clinical and electrophysiological evaluation of visual function was also studied. The obtained data served as normative data for ERG and VEP evaluation in infants and preschool children. Forty-five children aged from 1.5 months to 7.5 years participated in our prospective study. Ophthalmological and electrophysiological examination was performed in all subjects. The results show that visual acuity is rapidly improving during the first years of life and reaches maturity in the third year. Changes in parameters of electrophysiological responses as a function of age were also detected. A correlation between clinical evaluation of visual function and electrophysiological responses was confirmed. The obtained normative data for electrophysiological testing of infants and preschool children are now used atthe Visual Electrophysiology Unit of the Ophthalmology Clinic, Ljubljana Medical Center, as a significant aid in early detection of pathology of the entire visual pathway in infants and preschool children.
Keywords: Elektroretinografija; Child Development; Evocirani potenciali vidni; Vision; Visual Acuity; Otrok, razvoj; Electroretinography; Vid; Vid, ostrina; Evoked Potentials, Visual; oftalmologija; razvoj; otroci; child